Obstacles in Central African Agricultural Development and the Future Prospects - Kamba, Francklin; Wei, Shiqiang (Advances in Social Sciences Research Journal, 2016)
Located in the heart of Africa, Central African Republic is a vast country of 623 000km ², sharing the boarder with Chad, Cameroon to the west, to the south the Republic of Congo and the Democratic Republic of Congo and to the east Sudan and south Sudan. It has 4.5 million inhabitants, half of whom are below 18 (50%) and 62% live in the rural areas. The country is endowed with vast and varied natural resources: A good rainfall, a dense river network, and rich soils, large basement full of mineral resources, forests and diverse savannah and abundant wildlife. Despite these potentials, the country has moved in a cycle of impoverishment ,economic and socio-health continues to deteriorate, consequently increasing pressure on natural resources and accelerated environmental degradation. The economy is still dependent on agriculture in spite of the failure of crops. Agriculture remains the most contributing sector to the formation of national wealth as it represents 55% of GDP. This performance is not as a result of the improvement of agriculture, but is explained by lower secondary and tertiary sectors following the destruction of the means of production of the main industries. Agro-ecological conditions remain very favorable. It meets the needs of plants and allows diversification of agriculture production. Agriculture’s potential is estimated at 15 million cultivable hectares of which only about 0.7 million hectares are cultivated annually. Vegetation is much diversified, giving large pastures for transhumant livestock, and large forest reserves. Typology is distinguished by the following systems: cotton-food crop, livestock, coffee-food crop and livestock synergetic- tourism, food crop agriculture been a regular pressure with the conversion of former producers of cash crops (cotton, coffee and tobacco). Between 2008 and 2009, There was an increase of between 3.8 in 1104 to 100 tones in 1145 tones driven by the production of cassava the staple food of Central Africa. Without all these efforts and huge potentials, the results of agricultural are very low and the development is slow. In addition, environment and climate insecurities, explain the slow development of agriculture in Central African as well as primarily technical and technological skills. They are ways to find adequate solutions to these problems. This is through the exploitation of research themes centered on the management of agricultural land and conflicts between pastoralists and farmers, improvement of operational conditions, the integration of livestock into agriculture, adaption of a management board as a dynamic means of vulgarization. Establishing of partnerships in matters of research development or research themes which should highlight all the various problems raised by farmers and in the end, solutions could help develop the Central African agricultural sector.